1997
DOI: 10.3109/00016489709113424
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic Vestibular-Evoked Potentials in Normal Subjects: A Comparison Between Responses Obtained from Sternomastoid and Trapezius Muscles

Abstract: Brief intense clicks cause short latency microcontraction of cervical muscles. Several studies have supported the hypothesis that these microcontractions are of vestibular origin. Averaging these muscular responses enables us to obtain myogenic vestibular evoked potential (MVEP). The receptor of these responses is thought to be the saccule, afferent pathways being the vestibular nerve and efferent pathways the vestibulospinal tract. However, discrepancies are reported with regard to results obtained in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 15 publications
2
57
0
4
Order By: Relevance
“…In the literature 2,8,13,14,17,19,20,25,27,28,34 , it is reported that the trapezius and the sternocleidomastoid muscles allow a better recording of VEMPs, because it is easier to place the leads and there is higher muscle action potential triggering, necessary to obtain this potential, and its recording in the other anatomical regions is practically unfeasible.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the literature 2,8,13,14,17,19,20,25,27,28,34 , it is reported that the trapezius and the sternocleidomastoid muscles allow a better recording of VEMPs, because it is easier to place the leads and there is higher muscle action potential triggering, necessary to obtain this potential, and its recording in the other anatomical regions is practically unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies 2,[8][9][10][11][14][15][16]18,19,24,[28][29][30][31] , the stimuli were averaged by means of ear phones instead of the bone vibrators and the intensities were, usually, above 90 dBHL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations